Modeling dependency of micromirrors reflection in optical fibers components on the geometrical parameters - O. I. Filipenko; O. O. Chala; K. L. Khrustalev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The main goal of investigation is defining dependency of geometrical parameters of MEMS-mirrors components in opto-electro-mechanical switches to losses appeared in such systems. Geometrical parameters of mirrors such as roughness and curvature, which had appeared on stage of development, have influence on losses in fiber-optic communication lines. The modeling dependency of reflection possibility of micro-mirrors to values of roughness and curvature has been conducted.